Computational Insight into the Rope-Skipping Isomerization of Diarylether Cyclophanes - Thomas J. Summers (MDPI AG, 2021)
The restricted rotation of chemical bonds may lead to the formation of stable, conformationally chiral molecules. While the asymmetry in chiral molecules is generally observed in the presence of one or more stereocenters, asymmetry exhibited by conformational chirality in compounds lacking stereocenters, called atropisomerism, depends on structural and temperature factors that are still not fully understood. This atropisomerism is observed in natural diarylether heptanoids where the length of the intramolecular tether constrains the compounds to isolable enantiomers at room temperature. In this work, we examine the impact tether length has on the activation free energies to isomerization of a diarylether cyclophane substructure with a tether ranging from 6 to 14 carbons. Racemization activation energies are observed to decay from 48 kcal/mol for a 7-carbon tether to 9.2 kcal/mol for a 14-carbon tether. Synthetic efforts to experimentally test these constraints are also presented. This work will likely guide the design and synthesis of novel asymmetric cyclophanes that will be of interest in the catalysis community given the importance of atropisomeric ligands in the field of asymmetric catalysis.